analisis Loyalitas Pelanggan Dalam transaksi Pelanggan dalam Transaksi Pembelian Online Melalui Akun Jejaring Sosial instagram.com - Maria Kumalasanti (Sekolah Tinggi Ilmu Ekonomi SBI, 2015)
Along with the rise of online business development that occurs in social networking especially Instagram, researchers wanted to analyze customer loyalty in the online business transactions. Factor buyers satisfaction to the dimensions of the product and the level of response, the trust factor buyer to the dimensions of certainty and pragmatic attitude, the experience factor buyer in the dimension of pleasure and dimension reduction barriers affect customers loyalty in the purchase through a social networking site Instagram. Because in any business area, business people must expect loyal customers will affect revisiting, repurchase and recommend it to others.